COMPETENCY-BASED PERFORMANCE MANAGEMENT SYSTEMS: EFFECTS ON EMPLOYEE CAREER DEVELOPMENT - Tarini; Oktavianti; Rizki Eka Putra (RADJA PUBLIKA, 2025)
This study examines the critical competencies driving career advancement within modern organizations through a mixed-methods approach, combining survey data and qualitative interviews. Against the backdrop of evolving workplace demands, the research identifies four essential competency dimensions: technical skills, soft skills, leadership, and critical thinking. Results demonstrate that employees with balanced competency profiles achieve better promotion outcomes than those with specialized but asymmetrical skill sets. Furthermore, competency-based performance systems significantly enhance promotion transparency and talent development, with 75% of employees perceiving these systems as fairer and more motivating than traditional evaluations. The discussion emphasizes that integrated competency frameworks create synergistic benefits for both individual mobility and organizational sustainability. We conclude that strategically aligning competency development with talent management processes enables organizations to build agile, future-ready workforce while providing employees with clear, merit-based pathways for career growth.